Evaluation of The Toxic Effects of Some Male Sexual Enhancement Drugs in the Testes of Male Wistar Rats - Salami, Basirat Adedamola; Ogundimu, Opeoluwa Adebola; Adedoyin, Victor Sasaenia; Adeyemi-Ekeolu, Bukola; Olaleye, Omolara Adeola; Umezurike, Emeka Taye; Adegbehingbe, Kehinde Olusola; Akinde, Kehinde Mary (Journal of Science, Technology and Innovation Research, 2026)
Testicular damage is one of the most commonly reported adverse effect associated with many herbal drugs in Nigeria. This study evaluated the toxic effects of some male sexual enhancement drugs (ST and DB) in the testis of male Wistar rats. 18 male Wistar rats were randomized into three groups of 6 each. Group I received distilled water only, while others were administered 10 mL/Kg of ST and DB for 14 days respectively. Thereafter, the rats were sacrificed, the testes were harvested and testicular antioxidant concentration was evaluated. Rats treated with ST and DB had significantly (p<0.05) high malondialdehyde (MDA) activity compared to the control; catalase activity was significantly (p<0.05) low in rats administered ST while those administered DB had significant elevation in catalase concentration; superoxide dismutase (SOD) activity and reduced glutathione concentration (GSH) were was significantly (p<0.05) low in rats administered ST and DB; ST significantly increased, while DB significantly decreased the activity of glutathione-S-transferase. Testicular histology showed degenerative and necrotic changes in the seminiferous tubules. The GCMS results identified chemical compounds such as: 2,5-Furandione, 3-(dodecenyl) dihydro and 5-hydroxymethyfurfural which further raises concerns on the safety of DB and ST for oral consumption. These aphrodisiacs caused elevations in activities that are associated with cellular oxidative pathways as well as testicular damage. Thus, providing evidence that the aphrodisiacs may be unsafe for consumption and not strictly medicinal. Therefore, a more extensive chronic toxicity testing is recommended.